The Colorado magazine - State Historical and Natural History Society of Colorado.; State Historical Society of Colorado.; Colorado Historical Society. (State Historical and Natural History Society of Colorado, State Museum, 1923)
Current frequency: 4/year.Continues: State Historical and Natural History Society of Colorado. Bulletin of the State Historical and Natural History Society of Colorado, 1920-1923.Continued by: Colorado heritage, ISSN 0272-9377.Published by the State Historical and Natural History Society of Colorado, State Museum, 1923-1928; State Historical Society of Colorado, The State Museum, 1928-1976 ; by the Colorado Historical Society, 1977-1980.